The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.2172/6666173
|View full text |Cite
|
Sign up to set email alerts
|

Selective catalytic reduction of sulfur dioxide to elemental sulfur

Abstract: Elemental sulfur recovery from SO2-containing gas streams is highly attractive as it produces a saleable product and no waste to dispose of. However, commercially available schemes are complex and involve multi-stage reactors, such as, most notably in the Resox(reduction of SO2 with coke) and Claus plants(reaction of SO2 with H2S over catalyst). This project will investigate a cerium oxide catalyst for the single-stage selective reduction of SO2 to elemental sulfur by a reductant, such as carbon monoxide. Ceri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 0 publications
2
21
0
Order By: Relevance
“…However, in the case of 5CuC-100, 5CuC-200 and 5CuC-300, peak temperatures of a peak shifted to lower temperatures from 163 to 156 C and H 2 consumptions of b peak increased from 336 to 349 mmol g À1 cat . Obviously, the lower the peak temperatures of a peak were, the higher the activity of CuO2CeO 2 catalysts in preferential oxidation of CO was [18]. But H 2 consumptions of b peak had a contrary trend with the activity of CuO2CeO 2 catalysts, indicating that b peak played a slight role on the catalytic performance of CuO2CeO 2 catalysts [19].…”
Section: Article In Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the case of 5CuC-100, 5CuC-200 and 5CuC-300, peak temperatures of a peak shifted to lower temperatures from 163 to 156 C and H 2 consumptions of b peak increased from 336 to 349 mmol g À1 cat . Obviously, the lower the peak temperatures of a peak were, the higher the activity of CuO2CeO 2 catalysts in preferential oxidation of CO was [18]. But H 2 consumptions of b peak had a contrary trend with the activity of CuO2CeO 2 catalysts, indicating that b peak played a slight role on the catalytic performance of CuO2CeO 2 catalysts [19].…”
Section: Article In Pressmentioning
confidence: 99%
“…The PROX may be the most suitable method to reduce the amount of carbon monoxide to a level for use in electrochemical fuel cells [5]. The catalysts employed in the PROX include noble and nonnoble metal catalysts, while CuO2CeO 2 catalysts show a catalytic performance as well as, if not better than, noble metal catalysts [6][7][8][9]. Generally, preparation methods have a strong influence on the catalytic performance of CuO2CeO 2 catalysts [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…12 They concluded that only a small amount of copper is necessary to promote the CO oxidation. The excess of copper forms bulk CuO particles, which contributes little to the catalyst activity.…”
Section: A X-ray Diffractionmentioning
confidence: 99%
“…An exponential growth of published reports on gold and the plethora of the reactions it catalyzes has taken place over the last 25 years. This system was soon followed by a detailed structural and kinetic study by Liu and Flytzani-Stephanopoulos [54]. The CO oxidation reaction was first studied on Au/CeO 2 by Hoflund and co-workers [67].…”
Section: Gold/ceria Catalysts: Theoretical Studies Preparation Methomentioning
confidence: 99%